Impact of Malaysian industrial energy use on carbon dioxide emission - Abdullah Chik, Norlaila; Abdul Rahim, Khalid; Radam, Alias; Shamsudin, Mad Nasir (Universiti Putra Malaysia Press, 2013)
Environmental issues such as global warming and climate change have negative effects on Mother Nature resulting in floods, landslides, erosion and extreme heat. Otherwise, the positive effect on the economy subsequent to disaster is through the substitution of capital. Currently the Malaysian energy policy highly promotes energy efficiency and focuses on high value added sectors that produce less CO2 emission. This study attempts to identify the impact of Malaysian industrial energy use on CO2 emission by analyzing energy intensity and CO2 emission intensity. This study found that the transportation sector produced the highest value added but has the highest CO2 emission. The findings of this study will prompt energy policy makers to examine the sector and promote low carbon energy use among its users. At the same time the high value added (productivity) sectors should be encouraged to produce less CO2 emission to protect the environment. In order to reduce CO2 emission, the energy intensive sectors will also have to reduce energy consumption by adopting energy efficient technology that produces less CO2 in the future.